2018
DOI: 10.5004/dwt.2018.22365
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of a batch sequential contactor for the removal of chromium(VI) from industrial wastewater using sheep wool as a low-cost adsorbent

Abstract: a b s t r a c tCr(VI) removal from wastewater streams using sheep wool in sequential batch contactors (SBC) mode was investigated. The influence of the number of contactors on removal efficiency was also studied. SBC was carried out in tanks containing 100 and 1000 mL solutions. Four SBC runs ensured complete removal of Cr(VI) whereas three runs reduced its concentration from 100 to 0.06 mg/L. Experiments in both tanks gave similar results, thus permitting scalability to a pilot plant and eventual industrial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The following conditions from our previous work on batch sequential reactors [21] were used: Wool dosage = 8.0 g/L, contact time = 25 min, pH = 2.0, T = 25.0 • C, initial Cr(VI) concentration = 100 mg/L, and regeneration using 1.0-m KCl. For the first semi-continuous column trial shown in Figure 2, 100 mg/L Cr(VI) was fed into the adsorption column at pH 2.0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following conditions from our previous work on batch sequential reactors [21] were used: Wool dosage = 8.0 g/L, contact time = 25 min, pH = 2.0, T = 25.0 • C, initial Cr(VI) concentration = 100 mg/L, and regeneration using 1.0-m KCl. For the first semi-continuous column trial shown in Figure 2, 100 mg/L Cr(VI) was fed into the adsorption column at pH 2.0.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in solution pH accompanies the reduction that takes place when wastewater is processed, particularly during the 24 h dark period. Adsorption is highly dependent on pH, as results from batch studies indicate [21,23]. The optimum pH of 2.0 has led to ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies by our group, sheep wool has been found to be efficient in Cr(VI) removal, with subsequent reduction to Cr(III) [31,32]. This study reports on the results of using sheep wool for the removal of ARS from wastewater and the possibility of regenerating the contaminated wool.…”
Section: Introductionmentioning
confidence: 89%
“…That is why adsorption of metal cations is reported in several papers [6][7][8]. However, anion removal is also examined [9][10][11][12]. All the authors applied the adsorbate concentrations under 10 mmol/L probably because the increasing concentration decreases the removal percentage.…”
Section: Introductionmentioning
confidence: 99%